Landscape of in situ cytokine expression, soluble C-type lectin receptors, and vitamin D in patients with recurrent vulvovaginal candidiasis (2024)
The immunopathogenesis of recurrent vulvovaginal candidiasis (R VVC) is poorly understood. Recently, it was reported that patients with RVVC present a decrease in both the fungicidal capacity of neutrophils and the proliferative capability of peripheral blood mononuclear cells in response to Candida albicans infection, suggesting an alteration in the innate and adaptive immune response. The aim of this study was to determine the in-situ expression, in the vaginal mucosa, of genes associated with the immune response, as well as the serum concentrations of dectin-1, mannose-binding lectin (MBL), and vitamin D in patients with RVVC. A study was carried out on 40 patients with a diagnosis of RVVC and 26 healthy women. Vaginal scrapings were obtained, and the expression of genes that encode cytokines and transcription factors specific f or T h1, T h2, T h17, Treg, pro-inflammatory profiles, and enzymes related to oxidative/microbicidal mechanisms was evaluated by quantitiative polymerase chain reaction (qPCR). Additionally, serum levels of vitamin D and the soluble receptors dectin-1 and MBL were determined by enzyme-linked immunosorbent assay (ELISA). In patients with RVVC, a decreased expression of T-bet, ROR ?-T, IL-1 ?, and IL-17, and an increase in the expression of FOXP3, IL-4, IL-8, IL-10, and IL-18 were observed when compared to healthy women: moreover, decreased levels of MBL were also observed in these patients. These results confirm that patients with RVVC present in-situ alterations in both the specific and adaptive immune response against Candida spp., a fact that could be associated with the exaggerated vaginal inflammatory response.